Young Kohut and the Ancient Greek Satyr Play. Issue 1 (2nd January 2020) - Dobson, Marcia D.-S.
ABSTRACT: As a classicist and a self psychologist, my reading of Kohut's matriculation essay at the University of Vienna on Euripides' Cyclops, written when he was nineteen years old, suggests that he was an astute classical scholar and that his understanding of the Classics influenced his development of self psychological theory. In his reading of this play, Kohut treats dramatic characters as if they were patients to empathize with and understand; he looks at their relationships in a way that is later to emerge as a theory of self-selfobject relationships, and he is highly aware of the ways in which the hubris (arrogance) so often exhibited by characters in ancient Greek drama was incompatible with a development of a moral, civic life. I believe this understanding foreshadows his later ideas on narcissism, and that through the Cyclops he found the ominous influence of the Nazis in 1932 Vienna metaphorically mirrored in the socio-political crises of Athens in the late fifth century BCE. Heinz Kohut's essay was translated into English after 1956, at least 24 years after the original, in all probability by Kohut himself. It remains unpublished. This essay will bring to life the young Kohut through his earliest piece of extant writing and suggest his vibrant mind's creative and transformative views of psychoanalysis.